Stres dan Prokrastinasi Akademik pada Mahasiswa Pelaku Cyberslacking - Aully Grashinta; Ayu Gentary; Aisyah Syihab (Jurnal Ilmiah Psikologi MIND SET, 2022)
Distance learning gives students freedom to do multitasking behaviour including cyberslacking. Cyberslacking is the individual behaviour who use the internet during the lecturing process regardless of the ongoing learning process. This study aims to determine the effect of academic stress on academic procrastination in cyberslacking students. The participants in this study were 454 college students who did cyberslacking in distance learning. The Academic Procrastination Scale was used to measure academic stress and The Academic Procrastination Scale was used to measure academic procrastination. Data collected was analysed with multiple linear regression analysis technique. Result of this study shows that academic stress has a contribution on academic procrastination in cyberslacking students.